تقييم المتانة الإنشائية المتبقية للسفينة بعد حوادث التصادم باستخدام الطرق الرقمية - أحمد غالب; جورية نوار (Latakia University Journal -Engineering Sciences Series, 2017)
تُعتبر حوادث التصادم التي تتعرض لها السفن من أكثر الحوادث خطورة، وذلك بسبب النتائج الكارثية اللاحقة سواء فيما يخص الخسائر الاقتصادية في السفن والحمولات، والخسائر في الأرواح البشرية بالإضافة إلى التلوث البيئي الكبير الناجم عنها. لذلك تبذل المراكز البحثية على الدوام جهود كبيرة بهدف فهم وتحليل الاستجابة الإنشائية لبدن السفينة المتضررة نتيجة لهذه الحوادث. يهتم هذا البحث بتقييم المتانة الإنشائية المتبقية لسفينة مصدومة من خلال الطاقة الداخلية والإجهادات الإنشائية المختلفة المتولدة ضمنها. تم نمذجة حالة التصادم لناقلة نفط تتعرض للصدم من قبل المقدمة البصلية لسفينة أخرى عند قيم مختلفة لسرعة السفينة وزاوية الصدم، ثم درست المتانة الإنشائية للمقطع الوسطي للسفينة المصدومة اعتماداً على الطرق الرقمية باستخدام برنامج . مما سمح بوضع تصور واضح لتغيرات الإجهادات الإنشائية والطاقة الداخلية مع الزمن خلال عملية التصادم. Ship collision accidents are considered of the most serious incidents, due to the subsequent disastrous results both in terms of economic losses in ships and cargo, and the loss of human life as well as the great environmental pollution caused by it. Therefore, continuous efforts are being made by research centers in order to understand the structural response of the hull as a result of these incidents and accurately analyzed. This research is interested in assessing the residual structural strength of a ship exposed to collision through the internal energy and the various structural stresses generated within it. The case is modeled for an oil tanker exposed to collision by the bulbous bow of another vessel moves at different speeds and different angles. The structural strength of the middle section of the struck ship was analyzed based on the numerical methods using Ansys Dynamic Explicit program. Which allowed the development of a clear vision for the structural changes and internal stresses energy with time during the collision process.